EFFECT OF HUMAN CAPITAL DEVELOPMENT ON PERFORMANCE OF ABUJA ELECTRICITY DISTRIBUTION COMPANY IN NIGERIA - Farouk, Musa Adeiza; Salihu, Anazuo Saadat; Odeh, Blessing Patient (Kashere Journal of Management Sciences, 2024)
This study examines human capital development within the Abuja Electricity Distribution Company (AEDC) and its impact on organizational performance. It aims to identify challenges, gaps, and opportunities in human capital development within AEDC, assess the effectiveness of current initiatives, and explore correlations between human capital development and key performance indicators. Utilizing Human Capital Theory and Investment Theory of Human Capital, the research adopts a survey design covering AEDC staff from January 1, 2023, to December 31, 2023, with 4,276 staff members and a sample size of 366. Descriptive statistics, correlation analysis, and robust ordinary least squares regression are used for data analysis. Results indicate that increased investment in staff training negatively impacts organizational performance, while higher levels of skills and competence positively influence performance. Motivation shows a negative impact on job satisfaction and performance, highlighting the need for aligned motivation strategies. Enhanced employee well-being significantly improves performance, but job security negatively impacts performance, indicating the importance of factors beyond job security. The study concludes that staff training, skills, motivation, job satisfaction, and employee well-being are critical for AEDC’s performance, recommending prioritization of training needs, fostering competence development, aligning motivation strategies, and recognizing employee well-being’s significance beyond job security.